Male involvement in reproductive, maternal and child health: a qualitative study of policymaker and practitioner perspectives in the Pacific - Davis, Jessica; Vyankandondera, Joseph; Luchters, Stanley; Simon, David; Holmes, Wendy (Reproductive health, 2016)
The importance of involving men in reproductive, maternal and child health programs is increasingly recognised globally. In the Pacific region, most maternal and child health services do not actively engage expectant fathers and fathers of young children and few studies have been conducted on the challenges, benefits and opportunities for involving fathers. This study explores the attitudes and beliefs of maternal and child health policymakers and practitioners regarding the benefits, challenges, risks and approaches to increasing men's involvement in maternal and child health education and clinical services in the Pacific. In-depth interviews were conducted with 17 senior maternal and child health policymakers and practitioners, including participants from five countries (Cook Island, Fiji, Papua New Guinea, Solomon Island, and Vanuatu) and four regional organisations in the Pacific. Qualitative data generated were analysed thematically. Policymakers and practitioners reported that greater men's involvement would result in a range of benefits for maternal and child health, primarily through greater access to services and interventions for women and children. Perceived challenges to greater father involvement included sociocultural norms, difficulty engaging couples before first pregnancy, the physical layout of clinics, and health worker workloads and attitudes. Participants also suggested a range of strategies for increasing men's involvement, including engaging boys and men early in the life-cycle, in community and clinic settings, and making health services more father-friendly through changes to clinic spaces and health worker recruitment and training. These findings suggest that increasing men's involvement in maternal and child health services in the Pacific will require initiatives to engage men in community and clinic settings, engage boys and men of all ages, and improve health infrastructure and service delivery to include men. Our findings also suggest that while most maternal and child health officials consulted perceived many benefits of engaging fathers, perceived challenges to doing so may prevent the development of policies that explicitly direct health providers to routinely include fathers in maternal and child health services. Pilot studies assessing feasibility and acceptability of context-appropriate strategies for engaging fathers will be useful in addressing concerns regarding challenges to engaging fathers.